2009
DOI: 10.1007/s00415-009-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing structure and function of the afferent visual pathway in multiple sclerosis and associated optic neuritis

Abstract: The afferent visual pathway is commonly affected in MS. Assessment of the afferent visual pathway using clinical, imaging and electrophysiological methods not only provides insights into the pathophysiology of MS, but also provides a method of investigating potential therapeutic measures in MS. This review summarises the various assessment methods, in particular imaging techniques of the visual pathway. Retinal nerve fibre layer (RNFL) thickness is usually reduced following an episode of optic neuritis. Techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 105 publications
0
85
0
3
Order By: Relevance
“…More-extensive optic nerve lesions are associated with poor clinical outcomes such as slow and incomplete recovery. 81,82 Depending on the severity of inflammation, contrast enhancement can be observed on (fat-suppressed) T1-weighted images in about 94% of patients with acute optic neuritis. In established optic atrophy from previous damage, T2 high signal changes will also be seen, but these changes are associated with thinning of the nerve and do not change over time.…”
Section: Mri Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More-extensive optic nerve lesions are associated with poor clinical outcomes such as slow and incomplete recovery. 81,82 Depending on the severity of inflammation, contrast enhancement can be observed on (fat-suppressed) T1-weighted images in about 94% of patients with acute optic neuritis. In established optic atrophy from previous damage, T2 high signal changes will also be seen, but these changes are associated with thinning of the nerve and do not change over time.…”
Section: Mri Overviewmentioning
confidence: 99%
“…For assessment of the optic nerve, the MRI protocol must include fat-suppressed T2-weighted images (for example, short tau inversion recovery or frequency-specific selective partial inversion recovery) 81 and contrast-enhanced (fatsuppressed) T1-weighted images (Box 3). The most cost-effective approach is to use a standard dosage of gadoliniumbased contrast medium.…”
Section: Standard Care Protocolmentioning
confidence: 99%
“…4,5 Some TOS studies have shown that the optic nerve may be enlarged in acute ON, [6][7][8][9][10][11] though the validity of this technique for the diagnosis of ON has not yet been recog-nized. 12 No sonographic data are available to distinguish enlargement of the nerve itself from that of its sheath, though an enlargement of the sheath in acute ON has been described with MR imaging. 13 Previous studies did demonstrate good accuracy and reliability of sonographic quantification of optic nerve sheath diameter (ONSD).…”
mentioning
confidence: 99%
“…Conventional MRI has insufficient sensitivity and specificity to reveal the true extent of pathological changes occurring in MS, as normal appearing white matter may harbor different abnormalities, as seen in non-conventional MRI and pathological works 25 .…”
Section: Discussionmentioning
confidence: 99%